Different impulse control disorder evolution patterns and white matter microstructural damage in the progression of Parkinson’s disease - Hu, Ling; Lin, Changfu; Lin, Fabin; Wang, Lingling; Li, Zhenzhen; Cai, Zhijun; Liu, Xianghong; Ye, Qinyong; Wu, Yiwen; Cai, Guoen (Frontiers in Aging Neuroscience, 2023)
Background The course of impulse control disorders (ICD) varies in the early stage of Parkinson’s disease (PD). Aim We aimed to delineate the association between the evolution pattern of ICD and the progression of PD. Methods A total of 321 de novo PD patients from the Parkinson’s Progression Markers Initiative database were included. Patients were followed up for a mean of 6.8 years and were classified into different groups according to the evolution patterns of ICD. Disease progression was compared among groups using survival analysis, in which the endpoint was defined as progression to Hoehn and Yahr stage 3 or higher for motor progression and progression to mild cognitive impairment for cognitive decline. In the fourth year of follow-up, four types of ICD evolution patterns were identified: (1) non-ICD-stable (68.2%), a patient who is consistently free of ICD; (2) late-ICD (14.6%), ICD developed during the follow-up of patients; (3) ICD-stable (11.5%), patients showed persistent ICD; and (4) ICD-reversion (5.6%), baseline ICD disappeared during the follow-up of patients with ICD. Results The ICD-reversion type shows daily life non-motor symptoms [Movement Disorder Society-Unified Parkinson Disease Rating Scale (MDS-UPDRS) part I], daily life motor symptoms (MDS-UPDRS part II), rapid eye movement sleep behavior disorder, and anxiety symptoms has a greater impact. PD patients with different ICD evolution patterns had different changes in white matter microstructure at the onset of the disease. Those relevant brain regions are involved in ICD and non-motor functions. Conclusion Four early ICD evolution patterns are identified in de novo PD, with different prognoses and brain white matter microstructural damage patterns, and they may predict motor progression and cognitive decline in PD patients.